Pengembangan Prototipe Kompres Elektrik Berbasis Mikrokontroler untuk Terapi Hangat Dismenore - Agatha Mahardika Anugrayuning Jiwatami; Regina Dimeitri Ero Sura (General Engineering & Applied Science Journal, 2026)
Dysmenorrhea is a common complaint experienced by women during menstruation and may interfere with daily activities. Warm compress therapy is widely used as a non-pharmacological method to reduce pain; however, traditional compress methods have limitations in maintaining stable temperatures. This study aims to develop a microcontroller-based electric compress prototype capable of producing stable and controlled heat. The system was designed using a Positive Temperature Coefficient (PTC) heating element, DS18B20 temperature sensors, and a 16×2 I2C LCD display. Temperature control was implemented using Pulse Width Modulation (PWM) with an operating temperature range of 38°C to 45°C. System testing included temperature sensor testing, MOSFET module testing, temperature stability evaluation, and setpoint response testing. The results indicate that the system was able to maintain stable temperatures within the specified range and demonstrated good response to temperature adjustments. The developed prototype has the potential to become a practical and safe technology-based heat therapy device for dysmenorrhea pain management. Keywords: dysmenorrhea, electric compress, microcontroller, DS18B20, PTC heater